Clinical Studies on Ultrafractionated Chemoradiation: A Systematic Review - Scirocco, Erica; Cellini, Francesco; Zamagni, Alice; Macchia, Gabriella; Deodato, Francesco; Cilla, Savino; Strigari, Lidia; Buwenge, Milly; Rizzo, Stefania; Cammelli, Silvia; Morganti, Alessio Giuseppe (Frontiers in Oncology, 2021)
Aim. The efficacy of low-dose fractionated radiotherapy (LDFRT) and chemotherapy (CHT) combination has large preclinical but little clinical evidence. Therefore, the aim of this review was to collect and analyze the clinical results of LDRT plus concurrent CHT in patients with advanced cancers. Methods. A systematic literature search was conducted on PubMed using the PRISMA methodology. Only studies based on the combination of LDFRT (< 1 Gy/fraction) and CHT were included. Endpoints of the analysis were tumor response, toxicity, and overall survival, with particular focus on any differences between LDFRT-CHT and CHT alone. Results. Twelve studies (307 patients) fulfilled the selection criteria and were included in this review. Two studies were retrospective, one was a prospective pilot trial, six were phase II studies, two were phase I trials, and one was a phase I/II open label study. No randomized controlled trials were found. Seven out of eight studies comparing clinical response showed higher rates after LDFRT-CHT compared to CHT alone. Three out of four studies comparing survival reported improved results after combined treatment. Three studies compared toxicity of CHT and LDFRT plus CHT and all of them reported similar adverse events rates. In most cases toxicity was manageable with only three likely LDFRT-unrelated fatal events (1%), all recorded in the same series on LDFRT plus temozolomide in Glioblastoma Multiforme patients. Conclusion. The role of LDFRT plus CHT is not supported by robust evidence. However, most comparisons showed improved outcomes without worse toxicity.